2020
DOI: 10.29333/ejgm/7883
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Hypocalcemia after Thyroidectomy Stabilized with Magnesium

Abstract: We present the case of a 53-year-old woman who underwent total thyroidectomy as a multinodular goiter treatment, which after surgery presented hypocalcemia that did not reverse with combined therapy of calciotropic hormones and calcium supplementation. The symptomatology remission was reached only after the prescription of magnesium lactate tablets. It is known that hypocalcemia is the main complication of this surgery, however, little is known about hypomagnesemia and its role as a cause and consequence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Factors influencing early development of hypocalcemia post thyroidectomy may be attributed to failure of optimization of vitamin D levels prior to surgery, substernal goiter, total thyroidectomy, prolonged surgery time, female gender, perioperative Ca level changes, extent of central neck dissection, autoimmune diseases, malignancy and surgeon expertise [ 1 , 9 , 10 ]. On the other hand, Mg and phosphorus levels contribute to Ca homeostasis [ 6 , 7 ]; this perhaps is explained by the close-linked nature of deficiency of Mg and the impairment of PTH secretion and PTH receptor sensitivity [ 6 ]. However, a study conducted by Wang X, et al concluded that hypomagnesemia is not an independent predictor of hypocalcemia after total thyroidectomy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors influencing early development of hypocalcemia post thyroidectomy may be attributed to failure of optimization of vitamin D levels prior to surgery, substernal goiter, total thyroidectomy, prolonged surgery time, female gender, perioperative Ca level changes, extent of central neck dissection, autoimmune diseases, malignancy and surgeon expertise [ 1 , 9 , 10 ]. On the other hand, Mg and phosphorus levels contribute to Ca homeostasis [ 6 , 7 ]; this perhaps is explained by the close-linked nature of deficiency of Mg and the impairment of PTH secretion and PTH receptor sensitivity [ 6 ]. However, a study conducted by Wang X, et al concluded that hypomagnesemia is not an independent predictor of hypocalcemia after total thyroidectomy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a study conducted by Wang X, et al concluded that hypomagnesemia is not an independent predictor of hypocalcemia after total thyroidectomy [ 11 ]. In addition, hypocalcemia alongside hypomagnesemia is caused by the decreased Ca export from the bone due to the decrease of the PTH levels [ 6 , 12 ]. The selection of the proper Mg supplementation is not a particularly easy choice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum-ionized calcium undoubtedly contributes to the etiology of ischemic stroke by altering the cycle of cytotoxic events leading to ischemic cell death [19]. Low blood flow in the brain below [10][11][12][13][14][15] Case Report mL/100gr/min will provoke ischemia [20]. If the blood flow to the brain is reduced to 6-8 mL/100gr/min, there will be a disturbance in the adenosine triphosphate (ATP) pump causing an increase in extracellular potassium, intracellular calcium, and cellular acidosis leading to histologic cell necrosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…There are some risk factors that may increase the risk of hypocalcemia and hypomagnesemia after total thyroidectomy such as age over 40 years, female gender, hyperthyroidism, greater extent of surgery, post-surgery level of parathyroid hormone less than 8 pg/mL, post-surgery hypomagnesemia, diabetes, prolonged proton pump inhibitor intake, and teriparatide intake [ 11 , 12 ]. Some identified risk factors cannot be treated before, during, or after surgery; therefore, calcium carbonate, vitamins, and minerals are recommended for all patients undergoing thyroid surgery to prevent hypocalcemia symptoms [ 11 , 12 ]. The patient of the case report had several risks mentioned, of which are age, hyperthyroidism, and hypomagnesemia.…”
Section: Discussionmentioning
confidence: 99%